(untitled) (Innovations in Environmental Economics, 2025)
This study investigates how artificial intelligence innovation, banking development, and stock market capitalization shape ecological sustainability in the Nordic region from 1990 to 2020. Using the STIRPAT framework, the analysis first evaluates cross-sectional dependence and slope heterogeneity, revealing strong economic and environmental interlinkages among the countries. Mixed integration orders identified through first- and second-generation unit root tests support the application of the Panel Autoregressive Distributed Lag model to explore dynamic relationships. The findings indicate that economic growth, stock market expansion, and rapid urbanization intensify ecological pressure in both the short and long run. In contrast, advancements in AI innovation and the strengthening of the banking sector contribute to reducing environmental degradation, particularly over the long term, suggesting their potential roles in supporting cleaner production and efficient resource use. Evidence from the Dumitrescu–Hurlin causality test further shows unidirectional causal relationships running from AI innovation, stock market capitalization, and urbanization to the ecological footprint, while economic growth and banking development exhibit bidirectional causal interactions with environmental outcomes. Overall, the study provides timely empirical insights into how technological progress and financial system structures can be aligned with ecological objectives. These findings offer important guidance for policymakers seeking to integrate innovation-driven and finance-based strategies into sustainability planning across the Nordic economies.